Evaluation of immunization service delivery in government sector, Thailand, 2015 - วรินทร์เสถียร พอพิศ; ชอบธรรม เผด็จศักดิ์; เชื้อนาค ปิยะนาถ (Disease Control Journal, 2016)
This study aims for monitoring and evaluation of the immunization program’s performance at service delivery level in 3 key areas including quality of service delivery, vaccine management and cold chain and information system management. The study was conducted as a cross-sectional survey during February to July 2015. The evaluation team was composed of experts in 3 key areas (including quality of the immuni¬zation service delivery, vaccine management and cold chain and information system management) from the national immunization program at central level. The team monitored and evaluated the immunization perfor¬mance by using the national standard on immunization service for service delivery units as a guideline. The evaluation was performed through field visit and interview of the key responsible persons at service delivery units. Study sites were selected by multistage sampling from regional level to provincial and district level, and were not necessarily considered as representative of the country. One province was selected per each of the 12 regions, 3 districts were selected per province, and 1 district hospital and 1 sub-district health pro¬motion hospital (formerly health center) were selected per district. Total selected sites covered 72 service delivery units (36 provincial and district hospitals and 36 sub-district health promotion hospitals). A total of 46 service delivery units (63.9%) passed standard level of performance. Immunization service delivery is the area of work that reached the highest performance (90.1%) while the achievement information system got only 75.5%. In the area of vaccine management and cold chain monitoring, the study reveals that the sub-district health facilities had better in performance than the provincial and district hospitals with statistical significance (p<0.01). Furthermore in details, some areas were less satisfactory that included cold chain breakdown preparedness, proper vaccine requesting, completing and updating stock records, adverse events following immunization preparedness and response, and electronic data management system. Performance in immunization service delivery was relatively good in terms of quality of immunization service and cold chain management at service delivery unit. However there remained areas for further improvement. The key gaps concerned the quality of manpower in immunization. Therefore continuous training through training courses, refresher training, and regular supervision at the work sites are recommended.